A Comprehensive Analysis of Virtual Reality Applications in Healthcare - Woropo Albino Paiva, Hermenegildo; José Gelson Golçalves; Demostenes Zegarra Rodrígues; Renata Lopes Rosa (INFOCOMP Journal of Computer Science, 2024)
Abstract. Virtual reality (VR) has revolutionized the healthcare sector by introducing new methods of diagnosis, treatment, and medical training. This article presents a comprehensive analysis of VR applications in healthcare, exploring its advantages, challenges, and impacts. The review includes case studies and relevant literature, highlighting areas such as rehabilitation, surgical training, and exposure therapies. The results indicate that VR can enhance the effectiveness of treatments and the quality of medical training, offering immersive experiences that benefit both patients and healthcare professionals. Despite the promising advantages, challenges such as cost and specialized training remain. Future research should focus on developing more accessible solutions and expanding VR applications in medicine to ensure broader patient access to this revolutionary technology.